Visual impairment in FOXG1-mutated individuals and mice. (2nd June 2016) - Boggio, E.M.; Pancrazi, L.; Gennaro, M.; Lo Rizzo, C.; Mari, F.; Meloni, I.; Ariani, F.; Panighini, A.; Novelli, E.; Biagioni, M.; Strettoi, E.; Hayek, J.; et al.
Highlights: Foxg1 haploinsufficiency causes impairment of mouse and human visual function. Foxg1 +/Cre mice show defects in the visual cortex excitatory/inhibitory circuits. FOXG1 -related visual alterations are compatible with the blind-sight syndrome. Abstract: The Forkead Box G1 ( FOXG1 in humans, Foxg1 in mice) gene encodes for a DNA-binding transcription factor, essential for the development of the telencephalon in mammalian forebrain. Mutations in FOXG1 have been reported to be involved in the onset of Rett Syndrome, for which sequence alterations of MECP2 and CDKL5 are known. While visual alterations are not classical hallmarks of Rett syndrome, an increasing body of evidence shows visual impairment in patients and in MeCP2 and CDKL5 animal models. Herein we focused on the functional role of FOXG1 in the visual system of animal models ( Foxg1 +/Cre mice) and of a cohort of subjects carrying FOXG1 mutations or deletions. Visual physiology of Foxg1 +/Cre mice was assessed by visually evoked potentials, which revealed a significant reduction in response amplitude and visual acuity with respect to wild-type littermates. Morphological investigation showed abnormalities in the organization of excitatory/inhibitory circuits in the visual cortex. No alterations were observed in retinal structure. By examining a cohort of FOXG1 -mutated individuals with a panel of neuro-ophthalmological assessments, we found that all of them exhibited visual alterations compatible with high-level visual dysfunctions. In conclusion our data show that Foxg1 haploinsufficiency results in an impairment of mouse and human visual cortical function.